(untitled) (Al-Academy, 2016)
Artist kicks off in his production through creative artistic assimilation to the production of concepts and experiences, which can decode the artist blades through the re-built and converted to the subject of my mind according to the processes of analysis and synthesis. Artist need the expertise and experience to complete the technical work, and to develop taste aesthetic, and achieve certain goals belonging to Resume artist, diversity of artistic experiences between mechanism represents a female form and expression of contents and visions that carry letters of freedom in accordance with the creative visual surfaces embody the image of women, the main speeches adopted by propositions technical artists, and artists who relied female form and recall and employ them in done Plastic Optical two (Eugene Delacroix and Jawad Salim) and which form the subject matter current, where research includes the study of analytical comparison between the work of artists (Eugene Delacroix and Jawad Salim) regarding summoned shape and representations of women in their work. Find annexation of four chapters, the first chapter dealt with the research problem, and the importance of research, and the goal of the search, and determine the terms. Annexation of Chapter II three sections represented a theoretical framework, namely, (first section: assimilation concept), (second section: Display # Technical represent), (third topic: the freedom in the light of contemporary thought) as the detective included on the subtitles to enrich research, this as well as indicators theoretical framework and previous studies. The third chapter of search procedures, taking the research methodology, the research community, the limits of the research, curriculum analysis, and analysis of samples. The fourth chapter included the results and conclusions reached by the researcher, as well as the recommendations, and a list of sources and references, and a summary in English.